2019
DOI: 10.18697/ajfand.87.18565
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of mycotoxins in farm-stored wheat in Ethiopia

Abstract: In recent years, food safety has become an integral component of ensuring food security. Mycotoxin development in staple cereals is a principal threat to realizing food safety in developing countries. With the objective to investigate incidences and levels of mycotoxins in farm-stored wheat from major growing districts of Ethiopia, a study was conducted based on 179 samples collected from six districts: Wenberma, Merawi, Ofla, Hetosa, Gedeb, and Lemo. Total aflatoxins (AFT), Ochratoxin A (OTA), total fumonisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…These results are in agreement with the work carried out by Sangare-Tigori et al [38] who reported a high level of aflatoxin B1 and ochratoxin A contamination on maize from the Abidjan markets with concentrations ranging from <1.5 µg/kg to 20 µg/kg. Substantially equal results were also reported by Worku et al [39]. These authors detected concentrations between 6.3 -150 µg/kg and 2 -186.5 µg/kg for total aflatoxins and ochratoxin A in maize samples stored in five producing regions of Ethiopia.…”
Section: Discussionsupporting
confidence: 70%
“…These results are in agreement with the work carried out by Sangare-Tigori et al [38] who reported a high level of aflatoxin B1 and ochratoxin A contamination on maize from the Abidjan markets with concentrations ranging from <1.5 µg/kg to 20 µg/kg. Substantially equal results were also reported by Worku et al [39]. These authors detected concentrations between 6.3 -150 µg/kg and 2 -186.5 µg/kg for total aflatoxins and ochratoxin A in maize samples stored in five producing regions of Ethiopia.…”
Section: Discussionsupporting
confidence: 70%
“…A study in Gedeo zone, southern Ethiopia, that tested 150 maize samples from various sources including local markets and flour mills found that all the samples were contaminated beyond the safety level set by the EU (Chauhan et al., 2016). According to Worku and his colleagues, aflatoxin was detected in all stored maize samples collected from three regionals states of Ethiopia (Worku et al., 2019). Ayalew et al (2006) detected AFB 1 in 8.8% of the barley, sorghum, teff, and wheat samples collected from different parts of Ethiopia (Ayalew et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In feed ingredients, over 70% of samples from Kenya [10], Nigeria [8], and Ethiopia [23] were contaminated, with FBs at maximum levels of 11,831 µg/kg. However, less than 40% of maize samples from Ethiopia [23,29] and Tanzania [27] had detectable FBs but at levels up to 62,000 µg/kg. Unlike maize, peanuts and peanut products are not frequently contaminated with FBs, and less than half of samples from Nigeria [8,32] and Benin [28] contained FBs (max: 910 µg/kg).…”
Section: Fumonisinsmentioning
confidence: 99%